2004
DOI: 10.1007/s10096-004-1146-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mode of delivery and necrotising enterocolitis on the intestinal microflora in preterm infants

Abstract: To investigate the effects of mode of delivery and of necrotising enterocolitis on the faecal microflora, 140 infants born before 33 weeks of gestation were followed up for symptoms of necrotising enterocolitis. Stool samples for gas-liquid chromatography and culture were collected twice weekly, and, when necrotising enterocolitis was suspected, for 2 months. For each infant with necrotising enterocolitis (n=21), two control infants matched for birth weight and gestational age were selected from the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
80
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 26 publications
4
80
1
5
Order By: Relevance
“…The above studies, in conjunction with other findings (18,28), suggest that caesarean delivery may be a risk factor of NEC. Yet, the lack of controlled studies has left this clinically important question unanswered.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…The above studies, in conjunction with other findings (18,28), suggest that caesarean delivery may be a risk factor of NEC. Yet, the lack of controlled studies has left this clinically important question unanswered.…”
supporting
confidence: 73%
“…The patterns of bacterial colonization are particularly important for preterm neonates because of their increased sensitivity to bacterial colonization (9,29), with aberrant bacterial growth causing severe gut dysfunction and disease (15,37). Delivery mode and diet are determinants of initial colonization and development of the bacterial assemblages in the infant gut (17,18). Exemplary of this are the different densities of bacterial colonization, stability, and diversity among CS and VD neonates (15,17,37,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17,32 A narrowing spectrum of microflora presages the development of NEC. 15 Wang et al 33 demonstrated that preterm infants with NEC had a predominance of proteobacteria in the stool, and suggested that limited bacterial diversity and pathogenic bacterial predominance may contribute to the susceptibiity of premature infants to NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found an association between various bacterial species and NEC (15)(16)(17)(18)(19)(20), whereas others did not observe any association between NEC and any specific bacterial species (8,21).…”
Section: Discussionmentioning
confidence: 99%